2014
DOI: 10.4103/0974-620x.137138
|View full text |Cite
|
Sign up to set email alerts
|

Non-drainage scleral buckling with solid silicone elements

Abstract: Background:With the increasing number of cataract surgeries, incidence of posterior segment complications including rhegmatogenous retinal detachment (RRD) is likely to rise. Scleral buckling (SB) surgery is an effective and less expensive option. The primary advantage of non-drainage procedure is avoidance of possible complications associated with trans-choroidal drainage. The aim of present study is to describe the clinical profile of subjects undergoing non-drainage SB surgery with solid silicone elements f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…All eyes achieving primary anatomical success (84.6%) showed complete SRF absorption within 1 week, mean time of absorption being 3.14 days in our study. Similar study by Rishi et al found that complete absorption of SRF was seen in 75% eyes within 1 week and in 86% eyes within 6 weeks (Rishi, et al, 2014). Although some studies have reported correlation of SRF absorption with patients' age, subretinal precipitates, and duration and extent of RD (O'Connor, 1973) (Chignell, 1974); others have found no such association (Rishi, et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…All eyes achieving primary anatomical success (84.6%) showed complete SRF absorption within 1 week, mean time of absorption being 3.14 days in our study. Similar study by Rishi et al found that complete absorption of SRF was seen in 75% eyes within 1 week and in 86% eyes within 6 weeks (Rishi, et al, 2014). Although some studies have reported correlation of SRF absorption with patients' age, subretinal precipitates, and duration and extent of RD (O'Connor, 1973) (Chignell, 1974); others have found no such association (Rishi, et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Also they found no difference in the anatomical success between PPV and scleral buckling alone (Wong, et al, 2014). Rishi et al reported primary reattachment rate of 91.2% following non-drainage scleral buckling procedure (Rishi, et al, 2014). Haritoglou et al and Sasoh et al reported primary success rate of 84.7% and 91.2% respectively (Haritoglou, et al, 2010) (Sasoh, et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Scottish retinal detachment study published in 2011 reported primary success rate to be approximately 81% [11]. Rishi, et al performed non-drainage surgery in 306 eyes of 298 patients and reported primary anatomical success of 91% [12]. Proliferative vitreoretinopathy is one of the factor which can modify our approach to treat RD.…”
Section: Discussionmentioning
confidence: 99%
“…This might be one of the reasons for higher anatomic success in our study as we selected patients of 50 years or less. Scleral buckling results in terms of anatomic success are more or less the same when SRF is drained or not [3,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, the surgical complications are more in the SRF drainage group like sub-retinal hemorrhage, choroidal detachment, infections, vitreous and retinal incarcerations [2].…”
Section: Discussionmentioning
confidence: 99%